Serials Spoken Here: Reports of Conferences, Institutes, and Seminars. Issue 1 (2nd January 2016) - Blythe, Kurt; Martin, Susan J.; McCormick, Elizabeth; Rumler,, LeAnne
ABSTRACT: This quarter's column offers coverage of several sessions from the 35th Annual Charleston Conference, held November 4–7, 2015, in Charleston, South Carolina. The sessions detailed herein largely concern the optimal management of e-resources workflows and the evidence-based acquisitions models for e-resources.